Wundheilungsstörungen bei Rauchern, Nichtrauchern und nach Rauchstopp - Goertz, Ole; Kapalschinski, Nicolai; Kolbenschlag, Jonas; Daigeler, Adrien; Hirsch, Tobias (Der Chirurg, 2012)
BackgroundThe pulmonary and cardiovascular ramifications of smoking are well documented and this also applies to increased wound healing complications in smokers. The aim of this study was to ascertain whether preoperatively refraining from smoking would affect the incidence of wound healing disorders.Material and methodsBetween 2006 and 2008 a total of 295 patients underwent aesthetic (n = 167) or reconstructive surgery (n = 128). They were divided into three groups: A (n = 98) non-smokers for at least 2 years, B (n = 99) patients who refrained from smoking 6 weeks prior to surgery and C (n = 98) smokers. Smoking abstinence was verified by cotinine tests. Wound healing complications were defined as dehiscent wounds, wound infections, atypical scar formation and adiponecrosis.ResultsSmokers developed wound healing complications in 48.2% of cases, non-smokers in 21.0% and patients who had stopped smoking for 6 weeks in 30.8% of cases (p = 0.006).ConclusionElective surgery should only be performed on non-smokers and smokers who had refrained from smoking for at least 6 weeks to reduce wound healing complications as far as possible.
Gesehen am 17.10.2018